Memorializing the Holocaust: Schindler's List and public memory - Ott, Brian L., author; Gordon and Breach, publisher (Colorado State University. Libraries, 1996)
No effort to memorialize the Holocaust has been as far reaching in American culture as Steven Spielberg's 1994 film, Schindler's List. As a result of its nearly unanimous acclaim, Schindler's List is now being heralded as a watershed event in Hollywood. Reviewers hold it up as a model of how entertainment can be used to convey a serious educational message? In light of its cultural scope, this essay seeks to describe the relationship between the film and public memory surrounding the Holocaust. While Schindler's List is undoubtedly an aesthetic and artistic masterpiece, the author contends that it not only fails to create but structurally disallows self-reflective spaces for internal memory-work. Rather than prompting us to struggle with the difficult issues of the Holocaust, the film is structured in such a way as to completely shoulder our memory-burden. By analyzing its formal elements, the author demonstrates how Schindler's List fuels our desire for resolution and comfort which it then fulfills by constructing an ideologically conservative sanctuary for the spectator. The author concludes the essay by considering the social and political implications of such a project. In advancing the argument of this essay, the author does not wish to judge the film in any simplistic sense. There is much about the film that is important, provocative, and productive. The author believes it is possible to retain these elements while at the same time suggesting the film's principal shortcomings.
Brian Ott was a professor in the Department of Speech Communication at Colorado State University.
Keywords: spectator; historical document; dramatic film; memory-work; narrative